Multi-objective optimization of evaporation and condensation temperatures for subcritical organic Rankine cycle. (1st April 2015) - Xiao, Lan; Wu, Shuang-Ying; Yi, Tian-Tian; Liu, Chao; Li, You-Rong
Abstract: A multi-objective function F (X) by the incorporation of single-objective functions, i.e., net power output W net, exergy drop of the exhaust gas from inlet to outlet Δ E g, total exergy destruction rate I and system total cost C 2013, has been put forward as the subcritical organic Rankine cycle (ORC) performance indicator and solved with the method of linear weighted evaluation function. The optimization of the evaporation temperature T e and condensation temperature T c of subcritical ORC has been carried out by the use of pure working fluids R600a, R245fa, R601a, R601, R123, and non-azeotropic mixed working fluids R600a/R601a, R245fa/R601a, R245fa/R601, R600a/R245fa. The results reveal that there exist optimal evaporation temperature T e, opt and condensation temperature T c, opt minimizing the multi-objective function F (X); while T e, opt and T c, opt can not exactly exist when choosing single-objective functions, i.e., W net, I, C 2013 and Δ E g as the performance indicators. Although T e, opt and T c, opt vary with different working fluids, the ORC performance of mixed working fluids is not always better than that of pure working fluids. The multi-objective optimization of ORC shows superiority to the single-objective optimization, owning to its pursuit of the best comprehensive performance. Highlights: Multi-objective function incorporating four technical/economic indicators. Optimization of evaporation and condensation temperatures for subcritical ORC. Comparisons of multi-objective optimization with single-objective optimization. Performance comparison of ORC with pure and non-azeotropic mixed working fluids.